Краткий очерк истории Харьковского университета за первые сто лет его существования (1805-1905) - Багалей, Д.И.; Сумцов, Н.Ф.; Бузескул, В.П.; Bagaley, D.I.; Sumtsov, N.F.; Buzeskul, V.P. (Харьков: Типография Адольфа Дарре. Kharkov: Adolf Darre's Printing House., 1906)
Дмитрий Иванович Багалей (1857 — 1932) — историк, общественный деятель, член Государственного совета от Академии Наук и 9 российских университетов (1906), ректор Харьковского университета (1906—1910), Харьковский городской голова (1914—1917), академик УАН (с 1918).По окончании историко-филологического факультета Харьковського университета в 1880 году занимался преподаванием, научной, общественной деятельностью. Д. И. Багалей принимал живое участие в занятиях исторического общества летописца Нестора в Киеве и историко-филологического общества в Харькове. С 1918 — председатель историко-филологического отдела, член Президиума УАН. В 20-х годах преподавал историю Украины в высшей школе, одновременно исследуя историю Слободской, Левобережной, Южной Украины XV—XVIII веков. Владислав Петрович Бузескул (1858–1931) —историк-античник, историограф, академик АН СССР (1922), академик НАНУ (1925). Занимал должности приват-доцента и профессора Харьковского университета (1885—1924). Научно-литературная деятельность Бузескула весьма разнообразна, но главные труды его относятся к области древнегреческой истории. Несколько его работ посвящены истории Харьковского университета. Николай Фёдорович Сумцов (1854—1922) —фольклорист, этнограф, литературовед, историк. Член-корреспондент Императорской Санкт-Петербургской академии наук.Выпускник историко-филологического факультетаИмператорского Харьковского университета. Состоял приват-доцентом, ординарным профессором Харьковского университета и членом совета попечителя Харьковского учебного округа. Был председателем Педагогического отдела Историко-филологического общества при Харьковском университете. Член-корреспондент Императорской Санкт-Петербургской академии наук по Отделению русского языка (1905).Автор статей по малорусской и югославянской этнографии и словесности в Энциклопедическом словаре Брокгауза и Ефрона, многочисленных сборников украинской народной поэзии, этнографических исследований. В разных изданиях, преимущественно в «Киевской старине», «Этнографическом обозрении», «Сборнике Харьковского историко-филологического общества», «Русском филологическом вестнике» Сумцов напечатал около 300 исследований, статей и заметок, научных и публицистических. Bagaley Dmitry Ivanovich (1857 - 1932) - a historian, social activist, member of the State Council of the Academy of Sciences and 9 Russian universities (1906), Rector of the University of Kharkov (1906-1910), Kharkov mayor (1914-1917), Academician of the UAS (with 1918). After graduating History and Philology faculty of Kharkov University in 1880, he practiced teaching, scientific, and social activities. D. Bagaley took an active part in the chronicler Nestor activities of the historical society in Kiev, in historical and philological society in Kharkov. Since 1918 he was a chairman of the Department of History and Philology, member of the Presidium of the UAS. In the 20th years he taught the history of Ukraine in high school, at the same time researched the history of Sloboda, the Left Bank, the South of Ukraine during XV-XVIII centuries. Buzeskul Vladislav Petrovich (1858-1931), historian, historian, academician of the Academy of Sciences of the USSR (1922), Academician of the National Academy of Sciences (1925). He held the positions of assistant professor and professor of Kharkov University (1885-1924). Buzeskul ’s Scientific and literary activities are very diverse, but his main works are in the area of ancient Greek history. Several of his works are devoted to the history of the Kharkov University. Nikolai Fedorovich Sumtsov (1854-1922), folklorist, ethnographer, literary critic and historian. He was a corresponding member of the St. Petersburg Imperial Academy of History and Philology scientific alumnus of Imperial Kharkov University faculty. He was an assistant professor, ordinary professor of Kharkov University and a member of the Board of Trustees of the Kharkov school district. He was chairman of the Pedagogical Department of Historical and Philological Society at Kharkov University. He was a corresponding member of the St. Petersburg Imperial Academy of Sciences in the Department of Russian Language (1905). He was an author of articles about the Little Russian and Slavic ethnography and literature in the Encyclopedic Dictionary Brockhaus and Efron, numerous collections of Ukrainian folk poetry, ethnographic research. Sumtsov published about 300 research papers and notes, science and current affairs in various publications, mostly in the «Old days of Kiev», «Ethnographic Review», «Collection of Kharkiv Historical and Philological Society», «Russian Journal of Philology».
A short history of Kharkov University for the first hundred years of its existence (1805-1905)
Keywords: Харьковский университет; история Харьковского университета; основание Харьковского университета; университетское самоуправление; Kharkov University; Kharkov University foundation; the history of Kharkov University; university self-government